The Effect of Corporate Social Responsibility (CSR), Food Quality, and Perceived Value on Repurchase Intention Through Customer Satisfaction as Intervening Variables in The Pandemi Covid-19 Era (Study On "Chatime" Bubble Drink Products) - Mohc. Velian Muhajir; Tias Andarini Indarwati (Journal of Business and Behavioural Entrepreneurship, 2021)
Bubble drink products are one of the beverage trends that have developed this year, even during the Covid 19 pandemic. One of the bubble drink brands that is in demand by the public especially teenagers in Indonesia is Chatime, in which consumers do not buy Chatime just once. The purpose of this paper is to study the effect of corporate social responsibility, food quality, customer satisfaction, on repurchase intention, through customer satisfaction. The research sampling techniques used are nonprobability sampling by judgmental sampling. This study focuses on Chatime consumers who bought Chatime products during a pandemic Covid-19. The data analysis technique is used path analysis. The results show that CSR has a negative effect on repurchase intention and customer satisfaction, food quality has a positive effect on repurchase intention and customer satisfaction, perceived value has a negative effect on repurchase intention, but has a positive effect on customer satisfaction.